Against the Odds: Protection of Economic, Social, and Cultural Rights by the Constitutional Court of Ukraine - Yurii Sheliazhenko (Constitutional Review, 2020)
The article traces historical development, doctrine, and impact of constitutional review in Ukraine related to matters of social justice. It is shown that international review of Ukraine’s reports on observance of human rights obligations indicated a low level of compliance during the absence of independent constitutional review by the judiciary. After the establishment of the constitutional review, the compliance was improved against all doubts, whether socio-economic rights are justiciable in the Ukrainian context, and whether the judges are empowered enough to reshape authoritarian policies. Constitutional Court of Ukraine developed a doctrine of social justice based on the values of the rule of law, liberty, and equality, founding a pragmatic balance between the imperatives of individual freedom and economic security. In legal reasoning, judges implemented ideas of the human-centered state and personal autonomy in civil society, close to liberal democratic views, expressed by framers of the Constitution of Ukraine.